Investigating relative density effects on quasi-static response of high-density Rigid Polyurethane Foam (RPUF). (June 2022) - Iqbal, Naveed; Mubashar, Aamir; Ahmed, Sohail; Arif, Nabeel; Din, Emad-Ud
Abstract: This study aims at characterisation of various densities of Rigid Polyurethane Foam (RPUF) under quasi-static tension and compression. The density of foam is key parameter in selection of suitability for structural applications. Various densities of RPUF are synthesised using commercial grade Polyols and Methylene diphenyl isocyanate (MDI). The ratio of mixing both constituents was maintained at 1:1.15 for polyol and MDI respectively. Free rise density of the foam was achieved at 234 kg/m 3 and is considered the baseline density for comparison. The higher than baseline densities were achieved by blowing the mixture into a mould with variable pouring times and three densities in the range of 252 kg/m 3, 303 kg/m 3 and 353 kg/m 3 were achieved. The tensile and compression specimens were prepared from the manufactured blocks. SEM images were taken from the blocks of various densities and uniform cell patterns were observed for all densities. The specimens were then tested under compressive and tensile loads. It was found that the specimen exhibit consistency in results and the density affects the mechanical properties directly. Optimum density of foam for energy absorption capability of RPUF based on specific work done is also estimated. A phenomenological model based on relative density of foam was developed to assess material behaviour which can reduce the requirement of test specimens for obtaining a set of particular material properties. Graphical Abstract: ga1